the Role of E-Learning in Mathematics Learning at Muhammadiyah Sorong University of Education - Novita Wulandari; Mochamad Bruri Triyono; Jusrianto As; Ninik Septyani (Journal Research of Social Science, Economics, and Management, 2022)
Mathematics is one of the subjects that must be studied by students, especially students at the undergraduate level (S1). paying attention to the objectives of learning mathematics in Permendikbud Number 21 of 2016 requires students to have the ability to think logically, analytically, systematically, critical and creative. However, mathematics learning material that has an abstract nature, makes mathematics difficult by most students. This is one of the causes of not achieving the goal mathematics learning. The concepts can be understood easily when ease to follow the times experienced by students. Stage student development requires students to be able to reason with using things that are abstract and symbolic. One solution to help students understand mathematics material using e-learning. Learning E-learning is an educational concept that utilizes technological advances information and communication, especially in the teaching and learning process. Convenience learning with e- learning also lecturers can prepare learning effectively and efficient by using media and learning resources that are more interesting so that they do not focused on printed books. This can increase student interest in learning where learning is no longer focused on the lecturer and class. The function of e-learning in support learning activities in the classroom, namely as a supplement, complement and substitution. Based on the description of the explanation above, it can be concluded that: The purpose of writing this paper is to describe how the role of e-learning in learning mathematics at the Muhammadiyah University of Education Sorong.